1997
DOI: 10.1038/387179a0
|View full text |Cite
|
Sign up to set email alerts
|

Truncation of Kir6.2 produces ATP-sensitive K+ channels in the absence of the sulphonylurea receptor

Abstract: ATP-sensitive potassium channels (K-ATP channels) couple cell metabolism to electrical activity and are important in the physiology and pathophysiology of many tissues. In pancreatic beta-cells, K-ATP channels link changes in blood glucose concentration to insulin secretion. They are also the target for clinically important drugs such as sulphonylureas, which stimulate secretion, and the K+ channel opener diazoxide, which inhibits insulin release. Metabolic regulation of K-ATP channels is mediated by changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

57
891
7
11

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 718 publications
(967 citation statements)
references
References 19 publications
57
891
7
11
Order By: Relevance
“…Assembly of Kir6.2 with SUR enhances ATP-induced inhibition of the channel pore [25], and defines the tissue-specific burst kinetics of K ATP channel behavior [5,34,35]. Furthermore, fundamental K ATP channel properties, including stimulation by MgADP and potassium channel openers as well as inhibition by sulfonylurea drugs that are absent in truncated Kir6.2 channels, are rescued by co-expression of Kir6.2 with SUR [25,36].…”
Section: Kir62 Pore-forming Subunit: Site Of K Atp Channel Atp Inhibmentioning
confidence: 98%
See 3 more Smart Citations
“…Assembly of Kir6.2 with SUR enhances ATP-induced inhibition of the channel pore [25], and defines the tissue-specific burst kinetics of K ATP channel behavior [5,34,35]. Furthermore, fundamental K ATP channel properties, including stimulation by MgADP and potassium channel openers as well as inhibition by sulfonylurea drugs that are absent in truncated Kir6.2 channels, are rescued by co-expression of Kir6.2 with SUR [25,36].…”
Section: Kir62 Pore-forming Subunit: Site Of K Atp Channel Atp Inhibmentioning
confidence: 98%
“…The poreforming Kir6.2 subunits cannot readily traffic to the plasma membrane alone, without the regulatory SUR module, due to a C-terminal RKR endoplasmic reticulum retention signal [23,24]. When engineered to be expressed independently of SUR through truncation of the Cterminal amino acids, the Kir6.2 subunit was identified as critical for K ATP channel inhibition by intracellular ATP [25,26]. Although a conventional nucleotide binding motif has not been identified within the Kir6.2 sequence, photoaffinity labeling and scanning with sulfhydryl group reagents accomplished by mutagenesis identified that both N-and C-termini may contribute to recognition of ATP [27,28,29].…”
Section: Kir62 Pore-forming Subunit: Site Of K Atp Channel Atp Inhibmentioning
confidence: 99%
See 2 more Smart Citations
“…1) [13][14][15]. ATP maintains K ATP channel closure by binding to Kir6.2 [16,17], whereas ATP/ADP interactions with SUR secure the metabolic sensor function of the channel complex (Fig. 1A) [18][19][20].…”
mentioning
confidence: 99%